The Effectiveness of the CIPP Evaluation Model in Students’ Writing Skills - Hermayani, Shalma; Sholeh, Khabib; Purwanto, Joko (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2023)
So far, the evaluation of writing instruction has not fully considered comprehensive assessment aspects, causing students to struggle in effectively expressing their ideas in writing. Meanwhile, writing skills have become a crucial necessity in today’s era of technological advancement. This study aims to describe the implementation process and evaluation results of the CIPP model in learning writing skills in grade X at SMK Negeri 1 Purworejo for the 2024/2025 academic year. The research was conducted using a qualitative case study approach. Data collection techniques included literature review, observation, and note-taking. The literature review involved analyzing lesson plans designed by teachers, observation was conducted during learning activities, and note-taking was used to document findings from the observations. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data presentation, and data verification. The results were presented narratively, accompanied by tables and diagrams. The findings indicate a gap between planning and implementation in the evaluation process, yet the average writing skill scores demonstrate success. These findings highlight the importance of evaluation in learning to enhance effective writing skill development.